Potentially Life-Threatening Interaction between Opioids and Intrathecal Baclofen in Individuals with a Childhood-Onset Neurological Disorder: A Case Series and Review of the Literature - van Dijk, Liza M.M.; van Zwol, Annelies; Buizer, Annemieke I.; van de Pol, Laura A.; Slot, K. Mariam; de Wildt, Saskia N.; Bonouvrié, Laura A. (Neuropediatrics, 2024)
Background Spasticity and dystonia are movement impairments that can occur in childhood-onset neurological disorders. Severely affected individuals can be treated with intrathecal baclofen (ITB). Concomitant use of ITB and opioids has been associated with central nervous system (CNS) depression. This study aims to describe the clinical management of this interaction, based on a case series and review of literature.Methods Four individuals with childhood-onset CNS disorders (age 8–24) and CNS-depressant overdose symptoms after the concomitant use of ITB and opioids are described. The Drug Interaction Probability Scale (DIPS) was calculated to assess the cause-relationship (doubtful <2, possible 2–4, probable 5–8, and highly probable >8) of the potential drug–drug interaction. A literature review of similar previously reported cases and the possible pharmacological mechanisms of opioid–baclofen interaction is provided.Results After ITB and opioid co-administration, three out of four patients had decreased consciousness, and three developed respiratory depression. DIPS scores indicated a possible cause-relationship in one patient (DIPS: 4) and a probable cause-relationship in the others (DIPS: 6, 6, and 8). Discontinuation or adjusting ITB or opioid dosages resulted in clinical recovery. All patients recovered completely. In the literature, two articles describing nine unique cases were found.Conclusion Although the opioid–ITB interaction is incompletely understood, concomitant use may enhance the risk of symptoms of CNS-depressant overdose, which are potentially life-threatening. If concomitant use is desirable, we strongly recommend to closely monitor these patients to detect interaction symptoms early. Awareness and monitoring of the potential opioid–ITB interaction is essential to reduce the risk of severe complications.
Keywords: baclofen; opioids; respiratory depression; decreased consciousness; drug interaction